A Debreceni Egyetem díszudvarának panteonja - Gaál, Botond (Gerundium, 2013)
THE PANTHEON OF THE FORMAL COURTYARD OF THE UNIVERSITY OF DEBRECEN. In the plaques of the formal courtyard of the University of Debrecen 23 names are inscribed, which faithfully relect the mentality of the city, as well as its scientiic and scholarly signiicance. he pantheon is a replica of the rich store of Hungarian spirituality, which faithfully renders the speciic heritage of Debrecen and it also comprises within itself the values of Hungarian national culture in the spirit of universitas scientiarum. Based on thorough research, the study is the irst exploration of how the list of names of those chosen was established, and it ofers short biographies of the respective denizens of the pantheon.